Characterization and biological function of milk‐derived miRNAs. Issue 10 (31st July 2017) - Golan‐Gerstl, Regina; Elbaum Shiff, Yaffa; Moshayoff, Vardit; Schecter, Daniel; Leshkowitz, Dena; Reif, Shimon
Abstract : Scope: Breastfeeding is associated with reduced risk of infection, immune‐mediated disorders, obesity, and even cancer. Recently it was found that breast milk contains a variety of microRNAs (miRNAs) in the skim and fat layer that can be transferred to infants, and appear to play important roles in those biological functions. Methods and results: This study applied next generation sequencing and quantitative real‐time PCR analysis to determine the miRNA expression profile of the skim and fat fraction of human, goat, and bovine milk as well as infant formulas. Human and mammalian milk were found to contain known advantageous miRNAs in exosomes and also in the fat layer. These miRNAs are highly conserved in human, bovine and goat milk. However, they were not detected in several infant formulas. Further, miRNAs present in milk were able to enter normal and tumor cells and affect their biological functions. Following incubation of milk derived human miRNA with normal and cancer cells, the expression of miRNA‐148a was upregulated and the expression of the DNA methyltransferase1 target gene of miRNA‐148a was down regulated. Conclusion: These results reinforce previous findings on the importance of miRNA in breast milk. Future studies should concentrate on the addition of miRNA to infant formulas. Abstract : Breastfeeding is associated with reduced risk of infection, immune‐mediated disorders, obesity, and even cancer. Recently it was found that breast milk contains a variety of microRNAs (miRNAs) in the skim and fat layer that can be transferred to infants, and appear to play important roles in those biological functions. This study applies next generation sequencing and quantitative real‐time PCR analysis to determine the miRNA expression profile of the skim and fat fraction of human, goat, and bovine milk as well as infant formulas to infant formulas.